La place des dimensions subjectives au sein de la préparation linguistique des publics mobiles à l’ère de la mondialisation - Guzman, Laura (Neofilolog, 2023)
In the era of globalization, preparing language learners to deal with intercultural exchanges and to succeed in their mobility projects is a major issue. We think that subjective dimensions have a big role to play in mobile learners’ linguistic preparation. For us, there are some personal and existential dimensions in the mobility of qualified candidates who go overseas to complete their studies, or to have new work experiences in order to further their careers. These subjective dimensions must be taken into account if we want to help these learners to achieve their mobility goals. We will see how these dimensions can be included in French for specific purposes programs and courses by using the concept of “project.” We will also consider what kind of pedagogical material, based on corpora (“récit-témoignage”), can be proposed to encourage students to manage their language learning in an autonomous way and to use critical and strategic thinking when handling their mobility projects.